Experiential Learning to Support Digital and Artificial Intelligence Literacies in Postsecondary Education - Delanoy, Nadia (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2025)
This mixed-methods study examined how experiential learning theory (ELT) can support the development of digital and artificial intelligence literacies in postsecondary education through the integration of generative artificial intelligence (GenAI) tools. Guided by ELT’s four-stage cycle, concrete experience, reflective observation, abstract conceptualisation, and active experimentation, this study explored how students engaged with GenAI to enhance their learning, critical thinking, and ethical awareness. Data were collected from 17 students and one instructor through surveys and semi-structured interviews. Descriptive and thematic analyses revealed that students initially identified as beginners in GenAI use, employing the technology primarily for functional tasks such as organizing information or conducting surface-level research. Through experiential engagement and guided reflection, students demonstrated growth in confidence, ethical understanding, and critical evaluation of AI-generated outputs. Instructor findings converged with student perspectives, emphasizing the value of scaffolded, reflective engagement for literacy development. The integration of quantitative and qualitative results underscored the effectiveness of experiential learning in a GenAI-designed course.